Male Educators in Pre-School Education: Recognition or Anxiety? - Elena M. Kolesnikova; Irina A. Kudenko (Интеграция образования, 2023)
Introduction. Some parts of the education system, especially the pre-school and primary phases, remain almost exclusively “female” professional niches, and for years this dramatic gender imbalance in the educational workforce worldwide has been considered “natural” and not worthy of research. The situation has begun to change in the last two decades, as more and more researchers internationally have begun to study various aspects of male participation in early childhood education and care. The Russian academic community has been slow to join the debate, and Russian publications on males in Early Childhood Education and Care are next to naught. Materials and Methods. The authors used a diverse pool of primary and secondary information sources, such as official statistics, open source publications (content analysis of the texts of the “Kindergarten Dads” project) and newly collected empirical data (survey of 142 students of the Institute of Pedagogy and Psychology of Education of the Moscow City Pedagogical University (2022 year) and the vision of the Institute’s director, Professor A. I. Savenkov), to explore the following questions: 1) How many male educators work in the pre-school sector and in what capacity? 2) How are male educators represented in public and professional discourses? 3) What strategies have been used to attract more men into the sector and how successful have they been? Results. Despite the limitations of the available statistical data, some general conclusions can be drawn: the proportion of male pre-school educators in Russia has always remained extremely low. A peculiar combination of references to classical masculinity and gender equality in the construction of the image of a male educator. Summarizing the main results of the study, perhaps the most important point to highlight is the complexity and heterogeneity of teacher traineesʼ perceptions of the profession, their future, and male teachers. Discussion and Conclusion. Overall, our statistical analysis suggests that while barriers to more men entering the pre-school teaching profession are still prevalent and continue to create obstacles, they may not be as insurmountable as hypothesised and can be reduced, if not overcome, through targeted educational policies. Our case studies show that to be successful, recruitment and retention strategies need to address a range of common and male-specific barriers. These include changing the social image of pre-school sector as a female domain, improving pay and career prospects for some, if not all, types of jobs in the sector.